1998
DOI: 10.1038/sj.bmt.1701095
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic peripheral stem cell transplantation using positively selected CD34+ cells from HLA-mismatched donors

Abstract: Summary:and a preserved host immune system. Data on the effect of HLA mismatching on the incidence of graft failure showed We examined five children who underwent allogeneic an overall increase in the incidence in the mismatched peripheral stem cell transplantation (PSCT) using posigroup compared to HLA-identical sibling bone marrow tively selected CD34 ؉ cells from three or two loci-mistransplantation (BMT) and the frequency of graft failure matched donors. CD34 ؉ cells mobilized from peripheral increased as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 15 publications
0
23
0
Order By: Relevance
“…Takaue et al 36 investigated 41 children with leukaemia and NHL after unsorted autologous PBPC transplantation and showed abnormally low CD4 + counts and an inverse CD4/CD8 ratio for Ͼ12 months after treatment. Matsuda et al 15 reported five children having undergone CD34 + selected PBPC transplantation from allogeneic mismatched donors. The CD3 + cell counts remained low through the observation time of a maximum of 210 days after transplantion with CD4 + cells being more severely depressed than CD8 + cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Takaue et al 36 investigated 41 children with leukaemia and NHL after unsorted autologous PBPC transplantation and showed abnormally low CD4 + counts and an inverse CD4/CD8 ratio for Ͼ12 months after treatment. Matsuda et al 15 reported five children having undergone CD34 + selected PBPC transplantation from allogeneic mismatched donors. The CD3 + cell counts remained low through the observation time of a maximum of 210 days after transplantion with CD4 + cells being more severely depressed than CD8 + cells.…”
Section: Discussionmentioning
confidence: 99%
“…CMV infection is known to abrogate a successful T cell regeneration, as exemplified in one patient after CD34 + selected PBSC transplantation. 15 Third, the dose of CD34 + cells was high (median 7.1 × 10 6 CD34 + cells/kg). It has been shown that the period of time required for leukocytic and thrombocytic recovery after PBPC rescue is linked to the number of CD34 + cells used as a rescue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 3 shows a summary of pretransplant conditioning and GVHD prophylaxis regimens used for HLA-haploidentical donor transplantation in Japan. Infusion of purified CD34-positive cells from bone marrow [95] or peripheral blood mononuclear cells [96,97] after ATG-containing preconditioning has been studied in Japan as well, with a low incidence of acute GVHD.…”
Section: Gvhd Prophylaxis Regimens For Hla-haploidentical Donor Transmentioning
confidence: 99%
“…1,2 Few data are currently available in this field in patients with medulloblastoma. Matsuda et al 3 reported one child who obtained a short-lasting PR following allogeneic hematopoietic SCT for relapsed medulloblastoma. Lundberg et al 4 reported one patient who achieved CR lasting more than 2 years following allogeneic hematopoietic SCT for recurrent metastatic medulloblastoma.…”
mentioning
confidence: 99%